2013
DOI: 10.1002/0471140864.ps2706s73
|View full text |Cite
|
Sign up to set email alerts
|

Using Antibody Arrays to Measure Protein Abundance and Glycosylation: Considerations for Optimal Performance

Abstract: Antibody arrays provide a valuable method of obtaining multiple protein measurements from low volumes of biological samples. Antibody arrays can be designed to target not only core protein abundances (relative or absolute abundances, depending on the availability of standards for calibration), but also protein post-translational modifications, provided antibodies or other affinity reagents are available to detect the modifications. Glycosylation is a common modification that has important and diverse functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Several O-glycoproteome studies of serum have been undertaken in the past using PNA (35,52), and these have provided insight into the general presence of O-glycoproteins and O-glycosites in serum. Our interest was to isolate the small subfraction of circulating O-glycoproteins with aberrant STn O-glycosylation, which are predicted to exist from studies with the CA72-4 assay (53, 54) and lectin arrays (55)(56)(57)(58). High levels of STn are detectable in sera of patients with different cancer types (59 -61) and this is associated with lower survival (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…Several O-glycoproteome studies of serum have been undertaken in the past using PNA (35,52), and these have provided insight into the general presence of O-glycoproteins and O-glycosites in serum. Our interest was to isolate the small subfraction of circulating O-glycoproteins with aberrant STn O-glycosylation, which are predicted to exist from studies with the CA72-4 assay (53, 54) and lectin arrays (55)(56)(57)(58). High levels of STn are detectable in sera of patients with different cancer types (59 -61) and this is associated with lower survival (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…More specific reagents need to be used for screening and here the choice is much larger. Ideally an array approach is required and this is the current mode of study, with array technology using lectins [ 371 , 372 , 373 ] and antibodies [ 212 , 374 , 375 , 376 ]. This approach is in addition to the glycoarray platforms discussed earlier.…”
Section: Glycan Expression When the Gastrointestinal Microbiota Ismentioning
confidence: 99%
“…As an excellent protein research method, protein microarray has been extensively applied to measure AFP. [9][10][11] For instance, in our previous research, we have shown that the AFP serum level can be detected faithfully and correctly by protein microarray with a sensitivity of 91.67% and a specificity of 93.24%. 12 However, the serum level of AFP could also be increased in benign liver diseases, such as LC and hepatitis, and up to 40% of HCC patients' AFP levels can be normal.…”
Section: Introductionmentioning
confidence: 97%